Pengaruh Keteladanan Guru terhadap Kedisiplinan Peserta Didik - Herlina Herlina (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2020)
This research is motivated by various negative phenomena that are currently happening, such as people who live not according to how they should live. Starting from children who behave immorally, people who do not socialize well, adults who are not mature, and so on. This is identified as a bad impact of the low emotional intelligence they have. People who have emotional intelligence will be able to control themselves and regulate themselves so that they always do good and right things. Islamic religious education with perfect content, has provided humans with a series of rules and guidance for human survival. By studying Islamic religious knowledge and applying it in daily life, it will certainly affect a person's mindset, taste and behavior, which in turn will increase one's emotional intelligence. This research was conducted at the Islamic boarding school Muthmainnatul Qulub Al-Islami. This study aims to determine whether there is an influence of Islamic religious education on the emotional intelligence of students. The type of research used in this research is field research or field research with a quantitative approach, data collection techniques are questionnaires, documentation, and interviews. The sample in this study were 33 people with simple random sampling technique, the data obtained were then analyzed using the Product Moment correlation coefficient. Based on the results of data analysis with Product Moment correlation, the results obtained are values.